2002
DOI: 10.1002/prs.680210108
|View full text |Cite
|
Sign up to set email alerts
|

Using heats of oxidation to evaluate flammability hazards

Abstract: The heat of oxidation is the net heat of combustion per mole of oxygen consumed. For complete combustion it is given by 'AH/S" (kcal/mol oxygen), where 'AH, " is the net heat of combustion (kcal/mol fuel) and "S" is the stoichiometric ratio of oxygen to fuel as written in the stoichiometric equation. Although previously unrecognized, the heat of oxidation 4fiH,/S" is the single most powerful parameter for evaluating the flammability hazards of fuels. %his article derives and discusses eight simple rules for es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 8 publications
0
43
1
Order By: Relevance
“…Moreover, these theoretical descriptors have definite physical meanings, which are useful to probe the physicochemical information that has significant contribution to the LFL property. Regarding the statistical parameters of the models, both the MLR and NN models of work [7] were worse in terms of AAE and RMSE than the presented model. Moreover, the presented model is developed based on larger number of compounds in the dataset (830 versus 144), and also more compounds are employed in the test set for model external validation (208 versus 50).…”
Section: Comparison With Previous Modelscontrasting
confidence: 53%
See 2 more Smart Citations
“…Moreover, these theoretical descriptors have definite physical meanings, which are useful to probe the physicochemical information that has significant contribution to the LFL property. Regarding the statistical parameters of the models, both the MLR and NN models of work [7] were worse in terms of AAE and RMSE than the presented model. Moreover, the presented model is developed based on larger number of compounds in the dataset (830 versus 144), and also more compounds are employed in the test set for model external validation (208 versus 50).…”
Section: Comparison With Previous Modelscontrasting
confidence: 53%
“…Moreover, the presented model is developed based on larger number of compounds in the dataset (830 versus 144), and also more compounds are employed in the test set for model external validation (208 versus 50). Finally, regarding the applicability range of the models, the use of the models of work [7] requires extra data of needed physicochemical properties, and if only one of the needed properties is missing, calculation cannot be performed to predict the LFL. Oppositely, because only theoretical descriptors derived solely from the molecular structure is involved, the presented model would theoretically be used to reliably predict the LFL for any organic compound belonging to its applicability domain.…”
Section: Comparison With Previous Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Britton [11] summarizes flammability prediction rules for single and mixed organic fuels in air under atmospheric conditions. The author showed that the maximum flame temperature can be approximately computed as a function of the net heat of complete combustion, c H Δ , and the stoichiometric ratio of oxygen to fuel, S .…”
Section: Adiabatic Stoichiometric Flame Temperature Computationmentioning
confidence: 99%
“…That heat of oxidation ranges from 96 to 106 kcal/mol O 2 , with an average close to 100 kcal/mol O 2 . The combustion of hydrogen (H 2 ), carbon monoxide (CO), acetylene (C 2 H 2 ), formaldehyde (H 2 CO), ethylene oxide (C 2 H 4 O), and hydrazine (N 2 H 4 ) are examples of common exceptions to the above energy ranges (Britton, 2002). More recently, reliable and somewhat conservative estimates of both the lowest flammable concentration and limiting oxygen concentration for many fuels have been made using the heat of oxidation, or a combination of the heat of oxidation and the limit heat of combustion of fuel-air mixtures (Britton, 2002;Britton & Frurip, 2003).…”
Section: Introductionmentioning
confidence: 99%